Ebola virus disease: What should a dentist know? a brief review - Syed Wali Peeran; Syed Ali Peeran; Karthikeyan Ramalingam; Marei Hamad Al Mugrabi; Khaled Awidat Abdalla; Fatma Ahmed (Wolters Kluwer Medknow Publications, 2017)
Ebola virus disease (EVD) is a severe, fatal, zoonotic, hemorrhagic disease. The current outbreak is the largest in history and has spread across continents. Consequently, it has made the WHO to declare it as a public health emergency of international concern. To the best of our knowledge, it is the first comprehensive review of EVD and its implications for the dental fraternity.